The Impact of Leadership Style in the Overall System of a Business: Basis for Crafting an Intervention Program: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Business owners are entities or organizations that engage in professional activity. They maybe industrial, commercial, or other types. Setting and obtaining difficult goals in business,responding quickly when necessary, dominating the competition, and motivating others toattain their best potential. Ineffective management can harm the company and cause it to gobankrupt. Toxic workplace attitudes, staff segregation, the departure of high-performingworkers, and an unappealing workplace culture will all occur.The sole proprietorship and partnership groups of respondents' assets showed thatDemocratic had a 4.86 weighted mean and Coaching leadership styles got 4.56. Both had thegreatest overall impact on a business system, which is equal to Very Strongly Agree. Therespondents indicated that there are significant differences between the two sets ofrespondents' evaluations of the cited variables. One of the challenges faced by the two groupsof respondents is a lack of management skills.The main objective of this research was to identify the leadership style and improvementsrequired to support the growth and success of the company. There are four Leadership Stylesthat are in this study which are: Autocratic, Democratic, Coaching, and Laissez-faire. There isnever any doubt about who has the last say when an autocratic leader is in charge, whetherit's about a crucial business choice or how the organization is governed. Since one person is incharge in this leadership style setting, things typically go smoothly and efficiently when roles,rules, and procedures are clearly defined. Democratic leadership, a style of participantleadership, is a leadership style in which group members take a more participative role in thedecision-making process. Employees meet to discuss and resolve issues by giving everyonesome opportunity to contribute to decisions. Recognizing team members' abilities,motivations, and areas for improvement is a key component of coaching leadership.Meanwhile, laissez-faire leaders should give their followers the freedom to run their own desksand make their own judgments. When necessary, they provide their staff with help, direction,counsel, and training, but they rely on them to manage the specifics and carry out their jobsand projects.
Keywords: Business